12427 MKRN3 Methylation Abnormalities In Patients With Pubertal Disorders - Natalie C Grosek; Tharlyanne Wênia Santos da Silva; John C Magnotto; Antuono Latronico; Ana Pinheiro Machado Canton; Y. M. Chan; R S Carroll; Ursula B. Kaiser; Andre Luis Abreu (2024)
Abstract Disclosure: N.C. Grosek: None. T. Silva: None. J.C. Magnotto: None. A. Latronico: None. A.P. Canton: None. Y. Chan: None. R.S. Carroll: None. U.B. Kaiser: None. Background and Objectives: Central Precocious Puberty (CPP) is caused by early reactivation of pulsatile GnRH secretion before age 8 years in girls and 9 years in boys. Delayed puberty (DP) is defined by the absence or incomplete development of sexual characteristics by age 13 years in girls and 14 years in boys. Environmental cues affect the HPG axis and timing of puberty via epigenetic mechanisms such as DNA methylation (DNAm). Inactivating mutations in the maternally imprinted Makorin Ring Finger 3 (MKRN3) gene are the most common genetic defect associated with CPP, representing ∼9% of patients with sporadic and familial CPP. Genomic imprinting occurs through differential methylation of CpG islands at a gene promoter or enhancer region. Differentially methylated regions (DMRs) regulate genetic imprinting. We hypothesized that transcription factor binding sites (TFBS) for ZFP57 (CpG57) andNRF1 (CpGs54+55) within the islet 3.7kb upstream of MKRN3 (MRKN3 islet) may impact expression. This study aimed to analyze if aberrant MKRN3 islet DNAm changes are associated with disorders of pubertal timing. Methods and Results: Germline DNA from 2 control patients was used to analyze the MKRN3 promoter region and islet DNAm profile. Bisulfite-treated DNA was amplified by PCR with primers targeting MKRN3 promoter and islet and submitted to Sanger sequencing. All CpG islands in the promoter region were 100% methylated, but those in the MKRN3 islet were differentially methylated with ∼50-60% methylated. DNA from our CPP cohort (n=71) underwent Next-Generation Sequencing analysis of bisulfite-treated DNA of these regions to identify the DMR potentially associated with MKRN3 imprinting. The MKRN3 islet covered CpG59-CpG49. Next, samples from our CPP cohort and patients with DP (n=44) and normal pubertal timing (n=33; 45% prepubertal, 55% pubertal) underwent pyrosequencing analyses of MKRN3islet. To compare DNAm levels between controls and our cohorts at each CpG island, T-tests were used: reported as mean±SEM. In the CPP cohort, 4/11 CpGs were significantly hypomethylated compared to controls (CpGs 54, 53, 51, 50). Specifically, the NRF1 TFBS was hypomethylated compared to controls (37.8 vs 41.6 ± 1.1, p<0.001) and DP (41.4 vs 43.8 ± 0.83, p=0.044). In the DP group, we found no significant difference in DNAm compared to controls. But they had hypermethylation of 4/11 CpGs compared to the CPP group, including the NRF1 TFBS (CpGs 55, 53, 51,50). Neither the CPP nor DP cohorts had significant DNAm differences at the ZFP57 TFBS compared to controls. Conclusion: Our study showed hypomethylation of 4 out of 11 CpGs in MKRN3 islet, including the NRF1 TFBS, in CPP compared to control and DP groups. On the other hand, NRF1 TFBS was hypermethylated in DPP compared to CPP. Further studies are needed to determine if these alternations in methylation are associated with MKRN3 expression levels and pubertal initiation. Presentation: 6/1/2024